Understanding digital libraries - Lesk, Michael; Lesk, Michael (Boston : Elsevier, 2004)
This fully revised and updated second edition of Understanding Digital Libraries focuses on the challenges faced by both librarians and computer scientists in a field that has been dramatically altered by the growth of the Web. At every turn, the goal is practical: to show you how things you might need to do are already being done, or how they can be done. The first part of the book is devoted to technology and examines issues such as varying media requirements, indexing and classification, networks and distribution, and presentation. The second part of the book is concerned with the human contexts in which digital libraries function. Here youll find specific and useful information on usability, preservation, scientific applications, and thorny legal and economic questions. Useful for digital library projects in all kinds of settings, including commercial and community ventures, museums, research institutions, and schools. Covers the entire spectrum of media, including text, all kinds of images, audio, and video. Provides practical advice on achieving the best of what is possible while avoiding common pitfalls. Filled with case studies and references to valuable outside resources.
Chapter 1 Evolution of Libraries Chapter 2 Text documents Chapter 3 Images of pages Chapter 4 Multimedia storage and access Chapter 5 Knowledge representation schemes Chapter 6 Distribution Chapter 7 Usability and Retrieval Evaluation Chapter 8 Collections and Preservation Chapter 9 Economics Chapter 10 Intellectual property rights Chapter 11 International Activities Chapter 12 Future: ubiquity, diversity, creativity, public policy.
"Practical digital libraries, 2nd edition."
Includes bibliographical references (p. 387-411) and index.
Keywords: Libraries -- United States -- Special collections -- Computer files; Digital Libraries -- United States; Electronic books